2010
DOI: 10.1002/anie.201002888
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing by Weakening: Electrooxidation of Methanol on Pt3Co and Pt Nanocubes

Abstract: Loaded dice: High‐quality and similarly sized Pt3Co and Pt nanocubes were prepared by gradually reducing metal precursors at high temperatures. Cyclic voltammetric and chronoamperometric results show a much higher methanol oxidation current density on Pt3Co nanocubes (see picture). The enhanced catalytic activity was explained by the slower and weaker adsorption of CO onto Pt3Co.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(117 citation statements)
references
References 31 publications
6
110
0
1
Order By: Relevance
“…This agrees well with that observed by XRD (Fig. 6) and similar results have been reported for other Pt alloy NPs such as Pt-Co, Pt-Ni and Pt- Fe [28,31,54]. A SAED pattern of the Pt nanocubes shows the strong (200) diffraction ring and weak (111) diffraction ring (Fig.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This agrees well with that observed by XRD (Fig. 6) and similar results have been reported for other Pt alloy NPs such as Pt-Co, Pt-Ni and Pt- Fe [28,31,54]. A SAED pattern of the Pt nanocubes shows the strong (200) diffraction ring and weak (111) diffraction ring (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Xu et al [16] have also reported that PtCu nanocubes show a superior electrocatalytic activity towards methanol oxidation compared with spherical PtCu nanocubes and Pt nanocubes. Similar results have been observed on Pt 3 Co nanocubes [28] and Pt 3 Fe nanocubes [31] for electro-oxidation of methanol and formic acid respectively. Kang et al [20] reported that the PtMn nanocubes showed better electrocatalytic activities for a series of reactions (including oxygen reduction, formic acid oxidation, and methanol oxidation) than their spherical counterparts.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations